2010
DOI: 10.4314/njps.v23i1-2.54944
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistant pseudomonas aeruginosa in contemporary medical practice: findings from urinary isolates at a Nigerian university teaching hospital

Abstract: Summary: Pseudomonas aeruginosa is a bacterium that is often encountered in urinary tract infection (UTI) worldwide and has shown varied antibiotic susceptibility patterns. This study was therefore designed to ascertain the antibiotic susceptibility patterns of the organism in Jos. Data on antimicrobial susceptibility of P. aeruginosa generated from urine samples by the Microbiology laboratory of Jos University Teaching Hospital (JUTH) was compiled for a period of three years (July 2001-June 2004. Additional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
(23 reference statements)
11
9
1
Order By: Relevance
“…[11] suggested that this inhibitory action may explain the salutary effects of the macrolides on P. aeruginosa -associated chronic lung diseases, such as cystic fibrosis and diffuse panbronchiolitis. Contrary to the observation of this study, several reports have been documented on Pseudomonas resistance to clindamycin [57,58] and nitrofurantoin [58,59,60]. Whereas the tested isolates in this study exhibited intermediate sensitivity to the tetracyclines (tetracycline (40%), minocycline (60%)), nalidixic acid (70%), ampicillin/sulbactam (50%) and chloramphenicol (50%); reports in the literature suggests that Pseudomonas species were frequently resistant to these antibiotics [59,60,61,62].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[11] suggested that this inhibitory action may explain the salutary effects of the macrolides on P. aeruginosa -associated chronic lung diseases, such as cystic fibrosis and diffuse panbronchiolitis. Contrary to the observation of this study, several reports have been documented on Pseudomonas resistance to clindamycin [57,58] and nitrofurantoin [58,59,60]. Whereas the tested isolates in this study exhibited intermediate sensitivity to the tetracyclines (tetracycline (40%), minocycline (60%)), nalidixic acid (70%), ampicillin/sulbactam (50%) and chloramphenicol (50%); reports in the literature suggests that Pseudomonas species were frequently resistant to these antibiotics [59,60,61,62].…”
Section: Discussioncontrasting
confidence: 99%
“…However, Jombo et al . [59] reported sensitivity to chloramphenicol by P. aeruginosa strains isolated from urinary tract infection patients in Jos, Nigeria; while Lateef [52] observed Pseudomonal sensitivity to tetracyline in isolates from pharmaceutical effluents.…”
Section: Discussionmentioning
confidence: 99%
“…Antidrug profile of P.aeroginosa was represented in Table-3. Similar to the present investigations, Jombo et al(2008), Tamil et al(2011), Gonuigur et al(2003. Okon et al(2009), Gedamu et al(2014 and Hajira et al(2015) have reported 100% resistance to ampicillin by the isolate of P.aeruginosa; on the contrary only 45.4% of the resistance to ampicillin was shown by the isolates of Garba et al(2012).…”
Section: Mar Indexsupporting
confidence: 92%
“…This is in concordance with reports of other authors where MDR in P. aeruginosa has been reported. [23][24] S. maltophilia showed 100% susceptibility for ciprofloxacin and cotrimoxazole but was completely resistant to imipenem, amikacin and most of the other drugs. S. maltophilia is intrinsically resistant to most βlactams, including carbapenems.…”
Section: Discussionmentioning
confidence: 99%